SUITABILITY OF BIOLOGY TEACHER’S LEARNING OBJECTIVE AND AUTHENTIC ASSESSMENT - PANGASTUTI, ARDINI (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
This research aimed to describe suitability between learning objective and authentic assessment that made by certified biology teacher in Sidoarjo. This research is descriptive research with qualitative approach. Sample of this research is 27 certified biology teacher of 46 total population certified biology teacher in Sidoarjo. Techniques of collecting data done by documentation and gave self-assessment questionnaires teacher. Authentic assessment profile analysis result are known for 98,02% of teachers using authentic assessment. 98,02% of teacher who used authentic assessment, at 63,82% of teacher prepared learning objectives appropriate to the task and rubric. Keywords: learning objective, authentic assessment, Biology’s teacher